1999
DOI: 10.1007/pl00006610
|View full text |Cite
|
Sign up to set email alerts
|

Induced Metal Tolerance in Microbenthic Communities from Three Lowland Rivers with Different Metal Loads

Abstract: The response of microbenthic communities to sustained metal stress was studied in three lowland rivers with different levels of pollution. Tolerance against zinc and cadmium was determined in short-term toxicity tests with microbenthic assemblages colonizing glass discs. Photosynthetic activity served as an endpoint in tests for algae, whereas for bacteria thymidine incorporation was determined. For bacterial assemblages from unpolluted locations, EC50 values in short-term tests ranged between 6.7 and 56.2 &mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…These authors did not detect large differences between bacterial communities growing at Cu concentrations ranging from 3 to 87 M. Our results suggest that the complex and organized structure of the biofilm (10,18,30) would not protect the bacterial community in the same way that sediments do, even through the formation of extracellular polymeric substances was found to increase several resistance capacities of each encased organism (24) by reducing the bioavailability of heavy metals (33). Short-and long-term toxicity tests of heavy metals on aquatic biofilms have focused either on the response of the phototrophic compartment (1,2,5,17) or on that of the heterotrophic compartment (34), but toxic effect assessments based on physiological tests (3,19) or studies considering the biofilm as a whole have not investigated the effect of Cu (6,23). Possible interactions between phototrophic and heterotrophic compartments of a biofilm may be disturbed when one compartment is severely affected by a stress factor, e.g., an increase in toxicant concentration.…”
mentioning
confidence: 99%
“…These authors did not detect large differences between bacterial communities growing at Cu concentrations ranging from 3 to 87 M. Our results suggest that the complex and organized structure of the biofilm (10,18,30) would not protect the bacterial community in the same way that sediments do, even through the formation of extracellular polymeric substances was found to increase several resistance capacities of each encased organism (24) by reducing the bioavailability of heavy metals (33). Short-and long-term toxicity tests of heavy metals on aquatic biofilms have focused either on the response of the phototrophic compartment (1,2,5,17) or on that of the heterotrophic compartment (34), but toxic effect assessments based on physiological tests (3,19) or studies considering the biofilm as a whole have not investigated the effect of Cu (6,23). Possible interactions between phototrophic and heterotrophic compartments of a biofilm may be disturbed when one compartment is severely affected by a stress factor, e.g., an increase in toxicant concentration.…”
mentioning
confidence: 99%
“…We expected that due to a history of contaminant exposure, RCP isolates would be more tolerant to Cd than those isolates from EPA plants, and to some degree this was the case. The phenomenon of increased metal tolerance with preexposure has been described by others (Lehmann et al, 1999;Díaz-Raviñ a and Bå å th, 2001). Possible explanations for this initial lag phase followed by growth in cadmium could be due to time or concentrations necessary for induction of metal resistance efflux systems, or the time necessary for EPS production, or expression of additional adaptations.…”
Section: Discussionmentioning
confidence: 64%
“…Several phytoremediation studies have shown that rhizosphere bacteria contribute to plant metal tolerance and increased metal uptake (Crowley et al, 1992;De Souza et al, 1999;Salt et al, 1999;van der Lelie et al, 2000). Bacterial metal resistance has been described as a necessity for plantassociated bacteria in contaminated environments , and may be related to plant metal uptake, since the bioavailability of metals could be altered by expression of bacterial metal resistance systems (van der Lelie et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies showed that zinc pretreatment could enhance the tolerance of algae toward toxic metals others than zinc (e.g. Cd, Hg, Cu, Pb; Lehmann et al 1998;Tsuji et al 2002), so zinc-tolerant species could be good subjects of biosorbent, metallothionein or phytochelatin research (Andrade et al 2004;Perales-Vela et al 2006). To take these facts into consideration, it is reasonable to study the metal tolerance and removal ability of inland algal species, which could have relevant potential in water treatment.…”
Section: Introductionmentioning
confidence: 99%